Effects of Insecticides for Controlling Hogplum Beetle Podontia 14-punctata under Laboratory and Field Conditions - Uddin, MJ; Khan, MMH (Journal of Environmental Science and Natural Resources, 2015)
Experiments on hogplum beetle, Podontia 14-punctata were carried out to find out the suitable insecticide(s) with appropriate dose(s) for suppressing both larvae and adults. Results revealed that the highest mortality (100%) was found in 1st instar larvae after 24 hours at each dose of superior 505EC and the lowest mortality was in T4 treated leaves. The highest mortality was also found in 2nd, 3rd, 4th and adult stages of hog-plum beetle by T5 and T6 treatments. No mortality was observed in control treatment in laboratory trial. The mean number of larvae ranged from 1.5 to 7.6 per square meter of quadrate at one week after last spray. No significant difference was observed among treatments regarding percent leaf infestation at one day before 1st spray. The percent leaf infestation ranged from 5.01 to 9.82 at one week after last spray. The lowest percent (5.87%) leaf infestation was found in T6 treated plants while the highest percent (15.76%) leaf infestation was found in untreated control plants. The highest mortality was observed in T5 and T6 treated plants at all larval instars and no significant difference was found between two doses of each insecticide under field condition. The results of field trial also revealed that the minimum dose (0.75 ml L-1 of water) of Superior 505 EC is sufficient to suppress the field population of larvae and adults of Podontia 14-punctata effectively. Finally, it may be concluded that the highest mortality was found in all larval instars and adult stage of hog-plum beetle after 24 hours at each dose of superior 505 EC (T5 and T6 treatments) both in laboratory and field trials. J. Environ. Sci. & Natural Resources, 8(1): 79-83 2015